Competition and cooperation in social and political sciences : proceedings of the Asia-Pacific Research in Social Sciences and Humanities, Depok, Indonesia, November 7-9, 2016 : topics in social and political sciences /: proceedings of the Asia-Pacific Research in Social Sciences and Humanities, Depok, Indonesia, November 7-9, 2016 : topics in social and political sciences. (2017) - Unknown
No abstract available